2015
DOI: 10.5137/1019-5149.jtn.12537-15.0
|View full text |Cite
|
Sign up to set email alerts
|

Management of calvarial tumors - a retrospective analysis and literature review

Abstract: Hematogenous metastases to the calvarium can be caused by nearly all types of tumors (8). Most metastatic skull lesions being asymptomatic and less important clinically than intraparenchymal metastatic lesions, they are rarely diagnosed clinically but are frequently found in autopsies. Literature on the skull tumors consists mostly of individual case reports and a scarce number of case series. Only a few articles are available on skull metastases, especially calvarial metastases (3,4,13,15,16). Calvarial metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(37 citation statements)
references
References 8 publications
1
34
0
2
Order By: Relevance
“…Dissemination may occur due to direct extension or by hematogenic pathway, with cancer cells adhering to the endosteal surface and invading the bone marrow. 2,3,6 Breast, lung and prostate adenocarcinoma are the commonest primary lesions to metastasize to the skull due to a distinct bone tropism, but various other histologies have been reported. 14,15 Mitsuya et al reported 55% of skull metastases from breast cancer in a series of 175 patients, with a preponderance female versus male of 7:3 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dissemination may occur due to direct extension or by hematogenic pathway, with cancer cells adhering to the endosteal surface and invading the bone marrow. 2,3,6 Breast, lung and prostate adenocarcinoma are the commonest primary lesions to metastasize to the skull due to a distinct bone tropism, but various other histologies have been reported. 14,15 Mitsuya et al reported 55% of skull metastases from breast cancer in a series of 175 patients, with a preponderance female versus male of 7:3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Fat subtraction is important to determine tumor margins. 4,6 Management of calvarial metastases may depend on symptomatology, patient KPS, relationship with dural sinuses and eloquent cortex, histopathology, extent of spread and scalp infiltration. 3,5,6,16 Surgical treatment can be a safe palliative option for symptomatic patients, even when indicated after failed attempt with irradiation and/or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With CT, calvarial metastasis often presented as an osteolytic lesion. To better delineate lesion boundaries, as well as soft tissue and dural invasion, magnetic resonance imaging (MRI) with noncontrasted sequences was performed in several cases (2,(37)(38)(39). Cranial bone metastasis showed hypo-intensity on nonenhanced T1-weighted images and a variable appearance on T2-weighted images, in contrast with the hyper-intensity of normal bone marrow (21,28,31).…”
Section: Discussionmentioning
confidence: 99%
“…Metastases to the cranial bones are relatively rare, accounting for less than 5% of all secondary bone locations (1). At present, they remain a challenging disease to treat and current guidelines are mainly designed to address improvement in patients' quality of life (QoL) (2). Actually, there is lack of specific guidelines regarding the best therapeutic approach in cranial bone metastasis.…”
mentioning
confidence: 99%